The Study Of Lean Principles To Support The Environmental Management System (EMS) - Mohammad Rashidi, Razali (UTeM, 2011)
Lean and Environmental Management System (EMS) are widely used in the organization to enhance their performance and efficiency. ISO 14001 requires a commitment to continual improvement and lean principles will support EMS to achieve the continual improvement. The purpose of this study is to examine the characteristic of the lean principles into EMS and to propose linkage of the lean principles and EMS. To achieve the objective of the study, literature survey and quantitative research method using questionnaires survey are used. The findings of this study confirm that ISO 14001 certified company practice lean production practices. The study also proves that lean principles have positive and significant relationship with ISO 14001 EMS and the linkage can be made between lean principles and ISO 14001 to achieve Continual Improvement. The study is not limit on lean tools and technique but focus on the five lean principles with ISO 14001